The Role Of Family In Communication To Build Early Childhood Character - Aida, Elma Nur; Zulkarnaen, Z (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study examines how parental communication shapes character development in early childhood, specifically exploring the strategies parents employ to instill moral values and discipline in 4–5‑year‑old children at Kindergarten Aisyiyah Petoran, Surakarta. Methodology: Using a qualitative case study approach, researchers conducted semi‑structured interviews with both parents and their children to gather rich, firsthand accounts of communication practices and home dynamics influencing character formation. Results: Findings indicate that parents serve as primary role models, teaching moral and ethical values through positive behavior, open dialogue, and consistent, constructive discipline. Children were observed to imitate parental behaviors, underscoring the power of modeled conduct. Key elements identified include active listening and timely, supportive feedback, which bolster children’s confidence and capacity for emotional expression. A nurturing home environment—where children feel safe to voice thoughts and learn moral lessons—emerged as critical to fostering character growth. Applications/Originality/Value: By illuminating the specific communication strategies that effectively nurture young children’s moral development, this study deepens our understanding of family dynamics in early education. Its insights can guide parents, educators, and program designers in creating home‑and‑school partnerships that reinforce positive discipline, empathetic listening, and ethical role modeling to support well‑rounded character formation in early childhood.